O papel da área de controladoria nas empresas que adotam boas práticas de governança corporativa - Silva, Cristiane Dias (Universidade do Vale do Rio do Sinos, 2008)
This research investigates the responsibility of “the body” to manage accounting information in companies that operate in distinct segments of corporate governance (Level 1, Level 2 and New Market) of the São Paulo Stock Exchange (BOVESPA). Using empirical research, a survey was drafted to identify the profiles of the controllership area, the management model of the companies, the accounting function, the controllership function, participation in decision, etc. Data was collected and analyzed quantitatively, having obtained 33 answers representing 29% of the population. The results of the survey confirmed that most accounting functions are the responsibility of the controllership area of the companies. Regarding the participation of the controllership area in the decision process, it was observed that their role is one of counseling, a role that in 65% of the companies is simultaneously played to the role of control. Unable to identify how companies are managing this issue in order to preserve the independenc
Keywords: avalição; desempenho; governança corporativa; controladoria empresarial; corporate governance; evaluation; performance; companies controllership; Ciências Sociais Aplicadas